Simbol Budaya dan Pergeseran Adat Seksual dalam Tradisi Mandar - Muhammad Massyat; Unde, Alimuddin; Bahfiarti, Tuti; Karnai, Sudirman (LP2M IAIN Palopo, 2024)
This research explores the communication of traditional sexual customs in Mandar society, focusing on practices related to sexual relations. Although these practices are an integral part of Mandar cultural identity, social change and modernization have affected their understanding and application. Using phenomenological analysis, this study identifies the symbolic meanings, values and changes that occur in these customs and seeks to understand the role of verbal and non-verbal communication in their preservation or transformation. The findings reveal that symbols in traditional sexual rituals still have important meanings, reflecting values such as respect, family honor and social harmony. However, there have been noticeable changes in the way these symbols are understood and practiced, especially among the younger generation, who tend to interpret the customs from a modern perspective. These findings contribute to understanding how cultural symbols adapt in a changing social landscape, with broader implications for cultural preservation and communication studies in evolving societies.